Neuronal-glial chemical transmission mediated by glutamate and ATP - Verkhratsky, Alexei (Henry Stewart Talks, 2011)
Ionotropic receptors, Metabotropic receptors, Glutamate transporters, ATP: principal transmitter in neuronal-glial networks, Mechanisms of ATP release in the central nervous system, Ionotropic receptors and glutamate transporters mediating astroglial currents, Calcium permeability of astroglial NMDA and P2X1/5 receptors, Age-dependent remodelling of ionotropic receptors expression in cortical astroglia